Cancer prevention - Senn, Hansjörg; Kapp, Ursula (Recent Results in Cancer Research, 2007)
"This volume contains the main proceedings of the fourth international conference on ""Cancer Prevention 2006,"" which was held during February 16-18, 2006, in St. Gallen, Switzerland. Written by international experts in the field, the book comprises a comprehensive update on the most recent developments in the upsurging fields of molecular biology and cancer genetics and their interactions with clinical epidemiology and cancer prevention at various levels."